Accounting for adaptation and its effectiveness in International Environmental Agreements - Francesco Furini; Francesco Bosello (Environmental Economics and Policy Studies, 2020)
This paper analyses, within a standard International Environmental Agreement game, the effect of the introduction of adaptation on climate negotiation. The model expands the existing literature by considering a double relation between the two strategies. The common assumption that higher mitigation decreases the marginal benefit of adaptation and vice versa is enriched allowing for the possibility that mitigation, leading to lower and more manageable damages, determines a greater effectiveness of adaptive measures. We find the possibility for adaptation and mitigation to be strategic complements and not, as commonly believed, substitutes. Yet, as already known from the literature, the presence of adaptation can determine upward-sloping mitigation reaction functions regardless of the strategic relationship between mitigation and adaptation. When this is the case, the grand coalition can form. Nonetheless, large participation can induce substantive welfare gains only if adaptation and mitigation are strategic complements.
Keywords: C71; D62; D74; F53; H41; Q54; 330; Climate change; Adaptation effectiveness; Mitigation-adaptation strategic relation; International environmental agreements game